Potential Effectiveness of Point-of-Use Filtration to Address Risks to Drinking Water in the United States - Kathleen Ward Brown; Bemnet Gessesse; Lindsey J Butler; David L MacIntosh (SAGE Publishing, 2017)
Numerous contemporary incidents demonstrate that conventional control strategies for municipal tap water have limited ability to mitigate exposures to chemicals whose sources are within distribution systems, such as lead, and chemicals that are not removed by standard treatment technologies, such as perfluorooctanoic acid (PFOA)/perfluorooctanesulfonic acid (PFOS). In these situations, point-of-use (POU) controls may be effective in mitigating exposures and managing health risks of chemicals in drinking water, but their potential utility has not been extensively examined. As an initial effort to fill this information gap, we conducted a critical review and analysis of the existing literature and data on the effectiveness of POU drinking water treatment technologies for reducing chemical contaminants commonly found in tap water in the United States. We found that many types of water treatment devices available to consumers in the United States have undergone laboratory testing and often certification for removal of chemical contaminants in tap water, but in most cases their efficacy in actual use has yet to be well characterized. In addition, the few studies of POU devices while "in use" focus on traditional contaminants regulated under the Safe Drinking Water Act, but do not generally consider nontraditional contaminants of concern, such as certain novel human carcinogens, industrial chemicals, pesticides, pharmaceuticals, personal care products, and flame retardants. Nevertheless, the limited information available at present suggests that POU devices can be highly effective when used prophylactically and when deployed in response to contamination incidents. Based on these findings, we identify future areas of research for assessing the ability of POU filters to reduce health-related chemical contaminants distributed through public water systems and private wells.